Shooting analysis of Lithuanian national basktball men's teams in different age categories - Danilevicius, L.; Kreivyte, R. (Baltic Journal of Sport and Health Sciences, 2019)
Background. One of the most important problems for players, coaches and scientists is improving the accuracy of shooting the basket. It is the most important technique for playing basketball, and its dependence on performance is multifaceted. Methods. All 37 games in the 2015 European Championships in U16, U18, U20 and men`s national team were analyzed. Data was selected from the official boxscores of FIBA (International Basketball Federation). The following absolute game-related statistics were gathered: free-throws, 2-point and 3-point field goals (both successful and unsuccessful). The obtained values of the rate of success of 2-point, 3-point and free throw shooting were tested by the non-parametric Mann-Whitney U-test. The statistical analyses were performed using SPSS for Windows, version 20.0, and statistical significance was set at p < .05. Results. Comparing the number and accuracy of shots taken from 2-point distance, we found that there was no significant difference between men of different ages (p > .05). Most 3-point shots were done by U16 youth team, the least was in men`s national basketball team, a significant difference in the indicators (p < .05) was found between all the teams, except between men`s national team and U18 (p > .05). Comparing free-throws` indicators between different age groups, most throws were done by U16 team, the least were done by the U20 team (p<.05); however, there were no differences between the other significant indicators (p>.05). Comparing free-throws accuracy indicators between the different age groups of basketball teams, significant differences in indicators were found between men`s national basketball team and U20, U16 (p<.05). Conclusions. The count of 2-point shots made in Lithuanian different age basketball national team games was more or less similar. Most 3-point shots were made by U16 team and the national men`s team made least 3-pointers. The indicators of accuracy did not have a significant difference between national teams, except for free throws: men`s national team made these shots most accurately, opposite situation was with U16 team